Akseptasi Electronic Ticketing (Studi Pada Penumpang Pesawat di Provinsi Lampung) - Irawan Irawan (Politeknik Negeri Lampung, 2018)
This study empirically tested the acceptance of electronic ticketing study on airplanepassengers in Lampung Province, using model Technology Acceptance Model (TAM). Theproblems formulated to investigate in this research is how is the influence perception of youthand perception of benefit to attitude of using electronic ticketing to airplane passengers inLampung.The data were collected through survey method, by submitting questionnaires to respondents.The samples were taken by purposive / judgment sampling method to the user population thatis airplane passengers who have used electronic ticketing at least twice. The data wereprocessed from 100 respondents with structural equation model analysis technique (SEM)using software analysis of moment structure (AMOS) 18.The result of the data analysis indicates that exogenous construct variables perception of easeand perception of benefit have no significant effect on attitude of electronic ticketing usage onpassenger plane in Lampung.